RFID-based Positioning System in Complex Environments - Mudrik Alaydrus (LPPM ITB, 2011)
For effective identification of objects, Radio Frequency Identification (RFID) is used in miscellaneous activities. In recent times, RFID is also used for positioning purposes. We show a scenario of wireless propagation in free space observed by up to eight antennas with different polarization located in different positions. In this way, the polarization and diagram radiation of the antennas will play a significant role in producing electromagnetic field in the region. In the second case, the effects of disturbances in form of metallic boxes are studied. The determination of the position is carried out by fingerprinting procedure.